Digital Transformation in Early Childhood Education: Exploring the Role of Technology in Enhancing Learning Quality - Verawati Anjelly S; Angelina Paskah Br Haloho; Naila Aprilia; Rifki Ramadhan Sari; Kristian Nehemia Sianipar (Cakrawala Sekolah: Journal of Multidisciplinary School Education, 2026)
Early Childhood Education plays a crucial role in shaping children’s character, personality, and foundational skills during the critical early years of development. The rapid advancement of digital technology presents both opportunities and challenges for education, particularly in implementing engaging and adaptive learning strategies tailored to children’s developmental needs. This study aims to examine the urgency of early childhood education and to explore the role of digital technology in enhancing the effectiveness, innovation, and quality of learning processes. This research employed a qualitative approach using in-depth interviews and participant observation involving 16 participants, consisting of teachers and parents from Berlianta Education Foundation, Deli Serdang. The findings indicate that the integration of digital technology supports increased creativity, improved understanding of learning materials, and greater active participation among children. However, several challenges remain, including limited digital facilities, insufficient teacher training, and the potential risk of device dependency. The study concludes that strong collaboration among teachers, parents, and adequate institutional support is essential for creating modern, safe, and meaningful early childhood learning environments in an increasingly digital era.